2010
DOI: 10.1262/jrd.09-220t
|View full text |Cite
|
Sign up to set email alerts
|

Use of B-mode Ultrasound and Grey-Scale Analysis to Study Uterine Echogenicity in the Pig

Abstract: Abstract. This study was conducted to determine uterine echogenicity by grey-scale analysis (GSA) and transcutaneous ultrasonography in pregnant sows (P-sows; n=16) and gilts (P-gilts; n=13) vs. cyclic gilts (C-gilts; n=9) between days 8 and 16 post ovulation (po) with the aims of testing for feasibility of uterine GSA and of gathering reference data. Estruses and ovulations were hormonally synchronized and the animals artificially inseminated. Ovulation was monitored by ultrasound. The equipment used was a HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
13
0
4
Order By: Relevance
“…Very few studies have assessed pregnancy-induced changes in uterine echotexture in domestic animals. Of the handful that do exist, differences in uterine echotexture were observed in pregnant compared with cyclic sows from Days 11 to 15 [20]. Differences in uterine echotexture have also been observed from Days 7 to 13 between pregnant and cyclic cows [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have assessed pregnancy-induced changes in uterine echotexture in domestic animals. Of the handful that do exist, differences in uterine echotexture were observed in pregnant compared with cyclic sows from Days 11 to 15 [20]. Differences in uterine echotexture have also been observed from Days 7 to 13 between pregnant and cyclic cows [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…The endometrial echotexture decreases following ovulation, which is linked to edema (7,31). Kauffold et al (15) reported a notable increase in the MGL value during implantation in pigs. Cengiz et al (16) also reported a significant increase in the HOM value in pregnant goats 17 days after mating related to the implantation process.…”
Section: Discussionmentioning
confidence: 95%
“…While the echotextural changes in the endometrium were evaluated by visualizing ultrasonographic images in initial studies (7,31) two decades ago, computer-assisted image analysis systems are nowadays used in veterinary reproduction (14,15). By allowing quantitative evaluation, computer-assisted image analysis eliminates individual observation bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas últimas imágenes son compatibles con la presencia de colecta purulenta en la luz del útero. Sin embargo, en la práctica, estas imágenes no siempre se interpretan de manera correcta, dado que se necesita entrenamiento y experiencia por parte del operador (Almond et al, 2006;Kauffold et al, 2004Kauffold et al, , 2010.…”
Section: Endometritisunclassified